2023
DOI: 10.1186/s12903-022-02704-2
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis reveals miRNA crosstalk between periodontitis and oral squamous cell carcinoma

Abstract: Background Oral squamous cell carcinoma (OSCC) is one of the malignant tumors with a poor prognosis. Periodontitis (PD is considered a high-risk factor for OSCC, but the genetic mechanism is rarely studied. This study aims to link OSCC and PD by identifying common differentially expressed miRNAs (Co-DEmiRNAs), their related genes (Hub genes), transcription factors (TFs), signaling pathways, enrichment functions, and compounds, and searching for genetic commonalities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 82 publications
1
8
1
Order By: Relevance
“…However, the specific type of ubiquitin chain and E3 ubiquitin ligase that mediated c‐Myc degradation needs further exploration. Based on previous research findings, arecoline is a compound carcinogen that induces genetic mutations, DNA damage, and epigenetic abnormalities in somatic cells 45–48 . The changes in glycolytic pathways induced by arecoline in esophageal epithelial cells in our study may also involve genetic mutations or epigenetic abnormalities in esophageal epithelial cells.…”
Section: Discussionsupporting
confidence: 59%
“…However, the specific type of ubiquitin chain and E3 ubiquitin ligase that mediated c‐Myc degradation needs further exploration. Based on previous research findings, arecoline is a compound carcinogen that induces genetic mutations, DNA damage, and epigenetic abnormalities in somatic cells 45–48 . The changes in glycolytic pathways induced by arecoline in esophageal epithelial cells in our study may also involve genetic mutations or epigenetic abnormalities in esophageal epithelial cells.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, a recent study has revealed that CDH4 expression is up‐regulated in OSCC samples and highly related to survival of OSCC patients, which is positively associated with EMT, but negatively related to fatty acid metabolism and peroxisome pathways. Interestingly, CDH4 mediates the resistance to ferroptosis of OSCC cells, implying that CDH4 is a potential target for OSCC treatment 32 . Increasingly, studies have been focusing on discovering novel approaches to treat OSCC patients by inducing ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[22] At this time, patients can maintain normal respiratory, cardiovascular function and normal protective reflex. Liu et al [23] found that the time to reach the maximum sedation level after inhalation of N 2 O was 5 to 6 minutes, which was effective in pediatric patients. The success rate was 93.6%, and the incidence of adverse reactions was 3.95%.…”
Section: Management Methods and Commonly Used Drugs For Pediatric Den...mentioning
confidence: 99%